Design Thinking as a Tool for Participatory and Transformative Translator Education - Klimkowski, Konrad; Klimkowska, Katarzyna (Research in Language, 2021)
This article outlines the main tenets and the working cycle of Design Thinking, which is a problem-solving methodology. We argue that this methodology helps train qualities and skills that are particularly beneficial for students of translator education programmes. We recommend Design Thinking for translation teachers who subscribe to post-positivist, constructivist and other problem-based, participatory and collaborative educational approaches. The latter part of the article presents examples of classroom activities developed with the use of Design Thinking methodology. The activities focus mostly on communicative interactions between participants, since we believe that the major advantage of Design Thinking for the translation classroom is that it offers a structured scaffolding to improve classroom communication.